Transforming medical education to strengthen the health professional training in Viet Nam: A case study - Tuan D. Tran; Phuc M. Vu; Hong T.M. Pham; Luan N. Au; Hung P. Do; Hoa T.T. Doan; Nghia Huynh; Quynh T.V. Huynh; Bao K. Le; Dat Q. Ngo; Hanh T.M. Nguyen; Khanh D. Nguyen; et al. (Elsevier, 2022)
Summary: The competency-based undergraduate curriculum reform at the University of Medicine and Pharmacy at Ho Chi Minh City, Faculty of Medicine (UMP-FM) is detailed and reviewed in reference to the instructional and institutional reforms, and enabling actions recommended by the Lancet 2010 Commission for Health Professional Education. Key objectives are to: revise the overall 6-year curriculum to be more integrated and competency-based; reinforce students' knowledge application, problem-solving, clinical competence, self-directed learning and soft skills; develop a comprehensive and performance-based student assessment programme; and establish a comprehensive quality monitoring programme to facilitate changes and improvements. New features include early introduction to the practice of medicine, family- and community-based medicine, professionalism, interprofessional education, electives experiences, and a scholarly project. Institutional reform introduces a faculty development programme, joint planning mechanism, a "culture of critical inquiry", and a transparent faculty reward system. Lessons learnt from the curriculum reform at UMP-FM could be helpful to medical schools from low- and middle-income countries considering transitioning from a traditional to a competency-based curriculum. Funding: This work receives no external funding.